Letter from Edmund G. Brown, Alan Cranston, Thomas C. Lynch, Jesse M. Unruh, Joseph L. Alioto - Edmund G. Brown::::::; Alan Cranston::::::; Thomas C. Lynch::::::; Jesse M. Unruh::::::; Joseph L. Alioto:::::: (1969)
This October 17, 1969 letter from the Democratic Legislative Dinner Committee warns that the 1970 election is crucial because the legislature elected will control 1971 reapportionment and could allow Republicans to gerrymander the state if Democrats do not regain the State Assembly. It invites supporters to attend a fundraising dinner led by Senator Ed Muskie to promote party unity and help secure a Democratic legislative majority in 1970. Proceeds from the dinner will be held in trust and used in the following year's general election to support Democratic nominees.